Efektifitas Model Pembelajaran Course Review Horay Berbantuan Media Visual dalam Meningkatkan Kemampuan Berpikir Kritis Siswa pada Pelajaran Ekonomi Kelas X di MA Al Mansyuriyah - Safitri, Hilmiatul; Permana, Putut Said (Aufklarung: Jurnal Pendidikan, Sosial dan Humaniora, 2023)
This study aims to (1) determine the implementation of the Horay course review learning model in the experimental class; (2) identify the differences in critical thinking abilities between Grade X students in the experimental class, implementing the Horay course review learning model, and Grade X students in the control class, implementing the conventional learning model; and (3) assess the improvement in students' thinking abilities in the experimental class using the Course Review Horay learning model and the control class using the lecture method. The results of this study indicate that (1) the implementation of the Course Review Horay learning model assisted by Visual Media by the researcher has been well executed; (2) there is a difference in the average post-test results between the experimental class (18.74) and the control class (12.19); and (3) there is a significant improvement in students' critical thinking abilities between the experimental class and the control class at MA Al-Mansyuriyah.